Fire and Explosion Modelling of A Gas Transmission Pipeline in A Populated Residential Area - Ramadhani, Adhitya Ryan; Halfan, Ahmad (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2024)
Several oil and gas distribution pipeline routes pass through a highly populated residential area. Risk assessment based on consequence analysis is being considered to determine the level of danger to improve safety. This paper focuses on modeling the consequences of gas transmission pipeline leakage by reviewing the impact of explosions and fires. The TNT method and fireball modeling determined the overpressure and heat-flux at each radius. Variations of release volume, radius, and pressure were conducted to obtain heat-flux and overpressure values in several event scenarios. Sensitivity analysis using numerical analysis was conducted to determine the most influential parameters. It was found that the radius of the accident point is the main factor affecting the resulting impact, with a contribution of 86.1% for the fire scenario and 64.5% for the explosion scenario. The explosion and fire modeling results show that the safe zone from the accident point is at a radius of more than 500 meters.